Skin glaze ceramic tile and preparation process thereof
By adopting a three-layer structure of skin glaze layer on skin glaze ceramic tiles and using modified silicon oxynitride powder in the protective glaze layer, the problem of the reduction of glaze in the long-term use of skin glaze ceramic tiles is solved, achieving higher resistance Abrasiveness and gloss stability.
Patent Information
- Application Number
- CN202411457586.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-18
AI Technical Summary
Skin glaze ceramic tiles are prone to decrease surface gloss and reduce their appearance due to dust adhesion and infiltration during long-term use.
A three-layer structure of skin glaze layer, including a base glaze layer, a surface glaze layer and a protective glaze layer. The protective glaze layer is sintered from a specific ratio of protective glaze, containing modified silicon oxynitride powder to improve wear resistance and gloss degree stability.
It improves the wear resistance and gloss stability of the surface of ceramic tiles, avoids the phenomenon of dull and matte surfaces during long-term use, and maintains the beauty and performance of skin glaze ceramic tiles.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of ceramic technology, and in particular to a skin glaze ceramic tile and a preparation process thereof. Background Art
[0002] Among the current building floor materials, floor tiles with a glossiness of not less than 55 degrees are called bright tiles. They have a smooth surface and rich colors. They are often used for floor paving in indoor buildings, which can bring people a good visual experience. However, due to their high glossiness, they are prone to reflections. When the ambient light is high, they are prone to strong visual stimulation and cause people to feel uncomfortable. Therefore, skin-glazed ceramic tiles with a glossiness between 25-35 degrees and a delicate and smooth glaze feel have been widely used. Their surface presents a silky or sparkling luster, and the brick surface is delicate and moist. There is no strong reflection when the ambient light is strong, which can bring people a quiet and soft visual experience.
[0003] For example, the Chinese patent with publication number CN115557701A provides a glaze composition and skin-glazed ceramic tiles. By adopting a combination of multiple glazes with different ingredients and ratios, different melting changes can be produced during the firing process, which in turn causes the glossiness of different glaze layers to change, so that the skin-glazed ceramic tiles can maintain the glaze gloss between 25-35 degrees without the need for additional polishing, and will not be overly reflective and will not cause the interior space to be dim. However, after the ceramic tiles are laid on the floor of the building, they need to be used for a long time, and their service life often reaches 10-20 years. During long-term use, when dust adheres to the surface of the skin-glazed ceramic tiles and penetrates into them, it will greatly affect the glossiness of the skin-glazed surface, causing the surface of the skin-glazed ceramic tiles to be dull and the appearance to be reduced. Therefore, it is urgent to provide a solution to improve the above problems. Summary of the invention
[0004] The object of the present invention is to provide a skin-glazed ceramic tile and a preparation process thereof. The skin-glazed ceramic tile provided by the present invention has good wear resistance and can maintain the glossiness of the glaze during long-term use.
[0005] The present invention provides a skin glaze ceramic tile, comprising a ceramic tile body and a skin glaze layer sintered and formed on at least one surface of the ceramic tile body, the skin glaze layer comprising a base glaze layer, a surface glaze layer and a protective glaze layer sequentially formed along the ceramic tile body; the protective glaze layer is sintered and formed on the surface glaze layer by a protective glaze material, and the protective glaze material comprises, by mass: 50-60 parts of silicon dioxide, 7-10 parts of aluminum oxide, 1-2 parts of boron oxide, 2-3 parts of sodium oxide, 1-2 parts of potassium oxide, 15-20 parts of calcium oxide, 1-2 parts of magnesium oxide, 1-2 parts of lithium oxide, 0.1-0.5 parts of cesium oxide, 0.1-0.5 parts of barium oxide, 1-2 parts of zinc oxide, 1-2 parts of modified silicon oxynitride powder, 1-2 parts of adhesive and 1-2 parts of dispersant.
[0006] The skin-glazed ceramic tile provided by the present invention has a skin-glazed layer formed on the surface of the ceramic tile body, which can give the ceramic tile surface a skin-like feel, and can also reduce the surface reflection of the ceramic tile, that is, inhibit high light reflection. In addition, the skin-glazed layer can also protect the ceramic tile body, and prevent the ceramic tile body from breaking and internal cracks when subjected to impact and temperature changes. In addition, the modified silicon oxynitride powder is dispersed in the protective glaze layer, which can significantly improve the surface hardness and wear resistance of the protective glaze layer, effectively resist external friction and scratches, maintain long-term beauty, and improve the stability of the surface gloss of the protective glaze layer, avoiding the dullness and matte appearance of the surface during long-term use.
[0007] Optionally, the adhesive includes at least one of sodium carboxymethyl cellulose, polyvinyl alcohol, sodium silicate, methyl cellulose, and sodium alginate.
[0008] Optionally, the dispersant includes at least one of sodium polypropylene alcohol, sodium hexametaphosphate, and ethylenediamine di-o-hydroxyphenyl acetate.
[0009] Optionally, the average particle size of the modified silicon oxynitride powder is 1-20 μm.
[0010] Optionally, the preparation method of the modified silicon oxynitride powder includes: after surface activation of silicon oxynitride powder, stirring and dispersing in tetraethyl orthosilicate, separating to obtain a modified precursor; after surface hydroxyl modification of nano-molybdenum sulfide, ultrasonically mixing and dispersing with the modified precursor, separating and drying to obtain a modified intermediate; and nitriding the modified intermediate to obtain the modified silicon oxynitride powder. By surface activation of silicon oxynitride powder, the number of surface active sites of silicon oxynitride powder can be effectively increased, thereby improving the surface activity and surface reactivity of silicon oxynitride, which is conducive to surface modification in tetraethyl orthosilicate, and a silicon dioxide layer can be formed on the surface of silicon oxynitride powder, thereby improving the compatibility of silicon oxynitride powder in protective glaze, and at the same time, during the sintering process, the silicon dioxide on the surface of silicon oxynitride can be combined with the silicon dioxide in the protective glaze, thereby effectively improving the positional stability of silicon oxynitride in the protective glaze layer.
[0011] Optionally, the method for preparing silicon oxynitride powder comprises the following steps: preheating silicon oxide in an oxygen atmosphere at 300-400°C for 2-3h, heating the preheated silicon oxide to 1400-1500°C at a rate of 5-10°C / min in a nitrogen atmosphere, keeping the temperature for 20-30h, vacuum degassing at 200-300°C for 1-2h, and grinding to obtain silicon oxynitride powder. The silicon hydroxyl groups in the silicon oxide powder can be nitrided to silicon amino groups through the solid-gas nitridation reaction, and after vacuum degassing, the pores and defects in the silicon oxynitride powder can be reduced, and the structural stability of the silicon oxynitride crystals can be promoted.
[0012] Optionally, the silicon oxide has a particle size of 1-10 μm.
[0013] Optionally, the nitrogen-containing atmosphere includes one of nitrogen and ammonia.
[0014] Optionally, the silicon oxide is ball-milled in an oxygen atmosphere at 100-200° C. for 30-40 minutes, and then preheated in an oxygen atmosphere at 300-400° C. for 2-3 hours.
[0015] Optionally, the mass content of nitrogen in the silicon oxynitride powder is 20-40%.
[0016] Optionally, the silicon oxynitride powder is surface activated in an active agent, and the active agent includes at least one of hexadecyltrimethylammonium chloride, lauryldimethylamine oxide, and octadecyldimethylbenzylammonium chloride.
[0017] Optionally, after the silicon oxynitride powder is surface activated, it is stirred and dispersed in ethyl orthosilicate at a solid-liquid ratio of 0.1-0.3 g / mL.
[0018] Optionally, the modified precursor is prepared by stirring and dispersing in tetraethyl orthosilicate, separating and washing, and drying at 80-100° C.
[0019] Optionally, the average particle size of the nano-molybdenum sulfide is 1-100 nm.
[0020] Optionally, the surface hydroxyl groups of nano-silicon sulfide are modified in an alkaline solution, and the solute in the alkaline solution includes one of sodium hydroxide and potassium hydroxide.
[0021] Optionally, when the surface of the nano-molybdenum sulfide is ultrasonically mixed with the modified precursor, the modified nano-molybdenum sulfide and the modified precursor are ultrasonically mixed in anhydrous ethanol.
[0022] Optionally, the mass ratio of nano-molybdenum sulfide to the modified precursor is 1:(20-25).
[0023] Optionally, when the modified intermediate is subjected to renitridation to obtain the modified silicon oxynitride powder, the process includes: keeping the modified intermediate in a nitrogen atmosphere or an ammonia atmosphere at 1400-1500° C. for 5-10 hours, vacuum degassing, cooling and grinding to obtain the modified silicon oxynitride powder.
[0024] Optionally, the base glaze layer is formed by sintering a base glaze material on the ceramic tile body, and the base glaze material includes, by mass: 20-30 parts of aluminum oxide, 50-55 parts of silicon dioxide, 2-3 parts of potassium oxide, 10-15 parts of aluminum oxide, 10-15 parts of calcium oxide, 1-2 parts of magnesium oxide, 1-2 parts of sodium oxide, 1-2 parts of zinc oxide, 1-2 parts of sodium carboxymethyl cellulose and 1-2 parts of sodium hexametaphosphate.
[0025] Optionally, the surface glaze layer is sintered and formed by a surface glaze material on the base glaze layer, and the surface glaze material includes, by mass: 15-20 parts of aluminum oxide, 55-60 parts of silicon dioxide, 2-3 parts of potassium oxide, 10-15 parts of aluminum oxide, 10-15 parts of calcium oxide, 1-2 parts of magnesium oxide, 1-2 parts of sodium oxide, 1-2 parts of zinc oxide, 1-2 parts of cesium oxide, 1-2 parts of sodium carboxymethyl cellulose and 1-2 parts of sodium hexametaphosphate.
[0026] In a second aspect, the present invention also provides a preparation process of skin glaze ceramic tiles, comprising the following steps: spraying a protective glaze on the surface of the surface glaze layer, sintering at a high temperature of 1200-1300°C, and then grinding and forming to obtain skin glaze ceramic tiles; the spraying amount of the protective glaze on the surface of the surface glaze layer is 300-400g / m 2 .
[0027] In summary, the skin glaze ceramic tile provided by the present invention has the following beneficial effects:
[0028] 1. The surface of ceramic tiles has a skin-like feel. At the same time, it can reduce the surface reflection of ceramic tiles, that is, inhibit high light reflection, and has good mechanical properties and bonding strength.
[0029] 2. The modified silicon oxynitride powder is dispersed in the protective glaze layer, which can significantly improve the surface hardness and wear resistance of the protective glaze layer, effectively resist external friction and scratches, maintain long-term beauty, improve the stability of the surface gloss of the protective glaze layer, and avoid dullness and matte appearance of the surface during long-term use. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.
[0031] The present invention provides a skin-glazed ceramic tile, comprising a ceramic tile body and a skin-glazed layer sintered and formed on at least one surface of the ceramic tile body. Specifically, the skin-glazed layer formed on the surface of the ceramic tile body can give the ceramic tile surface a skin-like feel, and can also reduce the surface reflection of the ceramic tile, that is, inhibit high light reflection. In addition, the skin-glazed layer can also protect the ceramic tile body, preventing the ceramic tile body from breaking and internal cracks when subjected to impact and temperature changes.
[0032] The skin glaze layer includes a base glaze layer, a surface glaze layer and a protective glaze layer which are formed in sequence along the ceramic tile body. By setting the skin glaze layer as a three-layer structure, different glaze layers can give ceramic tiles different properties. For example, the base glaze layer can improve the bonding strength between the skin glaze layer and the ceramic tile to prevent the skin glaze layer and the ceramic tile body from peeling off during the sintering process, while the surface glaze layer can play a decorative role. For example, a variety of colors and patterns can be set in the surface glaze layer to meet the aesthetic settings of different consumers and different product models.
[0033] Specifically, the tile body in the skin glaze ceramic tile is sintered and formed using a ceramic tile blank, which can adopt a blank combination commonly used in the field for ceramic tile molding, so as to be able to maintain a stable shape after sintering.
[0034] The base glaze layer, surface glaze layer and protective glaze layer in the skin glaze layer have different chemical compositions. The protective glaze layer is sintered on the surface glaze layer. The protective glaze includes, by mass, 50-60 parts of silicon dioxide, 7-10 parts of aluminum oxide, 1-2 parts of boron oxide, 2-3 parts of sodium oxide, 1-2 parts of potassium oxide, 15-20 parts of calcium oxide, 1-2 parts of magnesium oxide, 1-2 parts of lithium oxide, 0.1-0.5 parts of cesium oxide, 0.1-0.5 parts of barium oxide, 1-2 parts of zinc oxide, 1-2 parts of modified silicon oxynitride powder, 1-2 parts of adhesive and 1-2 parts of dispersant.
[0035] Specifically, during the sintering process of the protective glaze, silica softens and begins to form a glass network after being cast at high temperature, providing a basic skeleton structure for the protective glaze layer, which can give the protective glaze layer basic strength and structural stability, while being able to penetrate into the surface glaze layer to increase the bonding strength between the protective glaze layer and the surface glaze layer. In addition, the stable chemical properties of silica itself can increase the protective glaze layer's resistance to erosion by chemicals such as acids and alkalis.
[0036] Specifically, during the sintering process of the protective glaze, alumina can interact with silica. First, part of the alumina will dissolve and compound in the glass network formed by silica to form a composite network structure to improve the adhesion and overall mechanical properties of the protective glaze layer. At the same time, alumina and silica can generate mullite crystals, which can not only greatly improve the hardness and thermal shock resistance of the glaze, but also adjust the refractive properties and glossiness of the protective glaze layer.
[0037] Specifically, during the sintering process of the protective glaze, boron oxide is pre-softened and interferes with the formation of a glass skeleton of silica, while increasing the fluidity of silica, which is beneficial to improving the surface smoothness and mechanical strength of the protective glaze layer. In addition, boron oxide can also reduce the melting temperature of the protective glaze as a whole, so that the glaze can form a uniform protective glaze layer at a relatively low temperature. Boron oxide can also be filled in the silica glass skeleton to fill the pores and defects inside the protective glaze layer, thereby increasing the surface sealing degree of the protective glaze layer, thereby increasing resistance to dust and pollution, and is beneficial to improving the performance of maintaining the surface gloss of the protective glaze.
[0038] Specifically, during the sintering process of the protective glaze, sodium oxide and potassium oxide can work synergistically with boron oxide, and the combined effect of the two can effectively reduce the sintering temperature of the protective glaze, thereby protecting the ceramic tile body and the bottom glaze layer and the top glaze layer on the surface of the ceramic tile body. In addition, sodium oxide can also adjust the glossiness and transparency of the protective glaze surface, so that the glossiness of the protective glaze surface is between 25-35 degrees to meet the light perception requirements.
[0039] Specifically, during the sintering process of the protective glaze, calcium oxide can fill the cracks and defects inside the protective glaze layer, thereby jointly with boron oxide to improve the surface sealing degree of the protective glaze layer and reduce the surface porosity and internal defect rate of the protective glaze layer. At the same time, calcium oxide can form calcium silicate crystals with silicon dioxide during the sintering process. Through the setting of calcium silicate crystals and mullite crystals, the glossiness and light refraction properties of the surface of the protective glaze layer can be comprehensively adjusted.
[0040] Specifically, during the sintering process of the protective glaze, magnesium oxide can form a silicon-magnesium compound with silicon dioxide, which can improve the chemical stability of the protective glaze layer. At the same time, magnesium oxide can also improve the corrosion resistance and anti-pollution performance of the surface of the protective glaze layer. In addition, magnesium oxide can also adjust the thermal expansion properties of the protective glaze layer to avoid excessive difference in the thermal expansion coefficient of the protective glaze layer and the surface glaze layer during the sintering process, resulting in glaze detachment.
[0041] Specifically, during the sintering process of the protective glaze, lithium oxide can react with silicon dioxide at a lower temperature, thereby destroying the glass phase structure and effectively reducing the melting temperature of the protective glaze, while greatly improving the fluidity of the protective glaze, so that the protective glaze can be well bonded to the surface glaze layer during the melting and sintering process, avoiding the occurrence of problems such as sagging and uneven thickness. In addition, lithium oxide can also improve the gloss and transparency of the protective glaze layer, thereby synergizing with other ingredients to stabilize the surface gloss of the protective glaze layer at 25-35 degrees.
[0042] Specifically, during the sintering process of the protective glaze, cesium oxide can change the surface tension of the protective glaze after it is melted, making it easier to spread the protective glaze evenly, thereby improving the surface flatness of the protective glaze layer. In addition, cesium oxide can also affect the crystallization process of crystals such as calcium silicate and mullite, thereby adjusting the optical and mechanical properties of the surface of the protective glaze layer.
[0043] The adhesive in the protective glaze can improve the bonding strength of the various components in the glaze to form a uniform mixture. At the same time, it can promote the glaze to adhere better to the surface of the glaze layer during the glazing process to prevent the protective glaze from falling off during the drying and sintering process. In addition, the adhesive gradually pyrolyzes during the sintering process, and some elements enter the protective glaze layer, and some elements are lost through gas burning to avoid affecting the performance of the protective glaze layer. The dispersant in the protective glaze can be compounded with the adhesive to prevent the various components in the glaze from agglomerating. At the same time, it can reduce the surface energy of the various components in the protective glaze, so that the various components in the glaze are evenly mixed during the sintering process, thereby adjusting the sintering thickness of the protective glaze layer.
[0044] Specifically, in the protective glaze, the adhesive includes at least one of sodium carboxymethyl cellulose, polyvinyl alcohol, sodium silicate, methyl cellulose, and sodium alginate, and the dispersant includes at least one of sodium polypropylene alcohol, sodium hexametaphosphate, and ethylenediamine di-o-hydroxyphenyl acetate.
[0045] In fact, the modified silicon oxynitride powder is evenly distributed in the protective glaze. During the sintering process of the protective glaze, the modified silicon oxynitride powder can significantly improve the surface hardness and wear resistance of the protective glaze layer, effectively resist external friction and scratches, maintain long-term beauty, and improve the stability of the surface gloss of the protective glaze layer, avoiding the dullness and matte appearance of the surface during long-term use. Specifically, after the silicon oxynitride powder is modified, the compatibility of the silicon oxynitride powder in the protective glaze can be effectively improved, thereby forming a stable glaze layer structure. In fact, the average particle size of the modified silicon oxynitride powder is 1-20μm.
[0046] Specifically, the preparation method of modified silicon oxynitride powder includes: surface activating silicon oxynitride powder, stirring and dispersing it in tetraethyl orthosilicate, and then separating to obtain a modified precursor; surface hydroxyl modification of nano-molybdenum sulfide, ultrasonically mixing and dispersing it with the modified precursor, and then separating and drying to obtain a modified intermediate; and complex nitriding the modified intermediate to obtain modified silicon oxynitride powder.
[0047] By activating the surface of silicon oxynitride powder, the number of surface active sites of silicon oxynitride powder can be effectively increased, thereby improving the surface activity and surface reactivity of silicon oxynitride, which is conducive to surface modification in ethyl orthosilicate. In fact, by soaking silicon oxynitride powder in ethyl orthosilicate, ethyl orthosilicate can form a silicon dioxide layer on the surface of silicon oxynitride powder through hydrolysis, thereby improving the compatibility of silicon oxynitride powder in the protective glaze. At the same time, during the sintering process, the silicon dioxide on the surface of silicon oxynitride can be combined with the silicon dioxide in the protective glaze, thereby effectively improving the positional stability of silicon oxynitride in the protective glaze layer.
[0048] In some embodiments, the preparation method of silicon oxynitride powder comprises the following steps: preheating silicon oxide in an oxygen atmosphere at 300-400°C for 2-3 hours, heating the preheated silicon oxide to 1400-1500°C at a rate of 5-10°C / min in a nitrogen atmosphere, keeping the temperature for 20-30 hours, degassing in a vacuum at 200-300°C for 1-2 hours and grinding to obtain silicon oxynitride powder.
[0049] By preheating silicon oxide in an oxygen atmosphere at 300-400°C, the impurities therein can be burned away, and the purity and oxygen content of silicon oxide can be increased. In addition, the preheated silicon oxide is subjected to high-temperature nitridation in a nitrogen-containing atmosphere, and the silicon hydroxyl groups in the silicon oxide powder can be nitrided to silicon amino groups through a solid-gas nitridation reaction. After vacuum degassing, the pores and defects in the silicon oxynitride powder can be reduced, and the structural stability of the silicon oxynitride crystal can be promoted.
[0050] In some embodiments, when silicon oxide is preheated in an oxygen atmosphere at 300-400°C, the average particle size of the silicon oxide used is 1-10 μm. By selecting silicon oxide with a small particle size, the contact area between the silicon oxide powder and the oxygen atmosphere can be increased, thereby forming a more reactive silicon oxide powder, which is beneficial for nitridation in a nitrogen-containing atmosphere. At the same time, silicon oxide with a relatively uniform particle size is beneficial for controlling the degree of nitridation.
[0051] In some embodiments, the nitrogen-containing atmosphere used includes one of nitrogen and ammonia. By adjusting the content of nitrogen in the nitrogen-containing atmosphere and the type of the nitrogen-containing atmosphere, as well as the nitriding temperature and nitriding time, the nitrogen content in the silicon oxynitride powder after nitridation and the structural characteristics of the silicon oxynitride crystal can be controlled. Specifically, the nitrogen mass content in the prepared silicon oxynitride powder is 20-40%.
[0052] In some embodiments, silicon oxide is ball-milled in an oxygen atmosphere at 100-200° C. for 30-40 minutes, and then preheated in an oxygen atmosphere at 300-400° C. for 2-3 hours. In fact, the particle uniformity of silicon oxide powder can be further improved during the ball milling process, and the defects on the surface of silicon oxide can be increased during the ball milling process, thereby further improving the surface activity of silicon oxide. Ball milling at 100-200° C. can form an oxide layer on the surface of silicon oxide and improve the activity of silicon oxide, which is beneficial to the diffusion of nitrogen atoms and the formation of silicon oxynitride.
[0053] In some embodiments, the silicon oxynitride powder is surface activated in an active agent. In fact, the silicon oxynitride powder can be surface activated in an active solution in which an active agent is dissolved, and specifically, the active agent includes at least one of hexadecyltrimethylammonium chloride, lauryldimethylamine oxide, and octadecyldimethylbenzylammonium chloride.
[0054] In fact, when the silicon oxynitride powder is surface activated in an active solution containing an active agent, conventional treatment steps such as ultrasonic dispersion, oscillation dispersion, and stirring dispersion can be used to promote uniform dispersion of the silicon oxynitride powder in the active solution. In addition, the solvent in the active solution must be selected to be able to dissolve the active agent and not react with the silicon oxynitride powder.
[0055] In some embodiments, after the silicon oxynitride powder is surface activated, it is stirred and dispersed in tetraethyl orthosilicate at a solid-liquid ratio of 0.1-0.3 g / mL. This is beneficial to improve the dispersibility of the silicon oxynitride powder in tetraethyl orthosilicate, avoid agglomeration and sedimentation of the silicon oxynitride powder in tetraethyl orthosilicate, and is beneficial to the coating modification of tetraethyl orthosilicate on the surface of silicon oxynitride.
[0056] In some embodiments, the surface activated silicon oxynitride powder is stirred and dispersed in tetraethyl orthosilicate, separated and washed, and dried at 80-100° C. to obtain a modified precursor. This is conducive to the hydrolysis of tetraethyl orthosilicate on the surface of silicon oxynitride powder to form a silicon dioxide coating structure.
[0057] In some embodiments, the surface of the nano-molybdenum sulfide is modified with hydroxyl groups in an alkaline solution, wherein the solute of the alkaline solution includes one of sodium hydroxide and potassium hydroxide, and the average particle size of the nano-molybdenum sulfide used is 1-100 nm. In fact, during the hydroxyl modification process, the hydroxide ions can react with the metal ions on the surface of the nano-molybdenum sulfide to form a metal hydroxide layer and introduce hydroxyl functional groups, which can improve the dispersibility of the nano-molybdenum sulfide and the mechanical properties in the glaze layer.
[0058] In some embodiments, the modified nano-molybdenum sulfide and the modified precursor are ultrasonically mixed in anhydrous ethanol. Ultrasonic mixing in anhydrous ethanol is beneficial to remove impurities mixed on the surface of the nano-molybdenum sulfide and the modified precursor, and is also beneficial for the nano-molybdenum sulfide and the modified precursor to be uniformly compounded. In fact, the mass ratio of nano-molybdenum sulfide to the modified precursor is 1: (20-25).
[0059] In fact, when the modified intermediate is subjected to complex nitridation to obtain the modified silicon oxynitride powder, the process includes: keeping the modified intermediate in a nitrogen atmosphere or an ammonia atmosphere at 1400-1500°C for 5-10 hours, vacuum degassing, cooling and grinding to obtain the modified silicon oxynitride powder. In fact, complex nitridation can improve the surface structure of the modified material and introduce the element on the inner surface of the modified intermediate, thereby effectively improving the dispersibility of the modified silicon oxynitride powder in the glaze layer and improving the structural stability of the modified silicon oxynitride powder.
[0060] In some embodiments, the base glaze layer is sintered and formed by a base glaze material on the ceramic tile body, and the base glaze material includes, by mass, 20-30 parts of aluminum oxide, 50-55 parts of silicon dioxide, 2-3 parts of potassium oxide, 10-15 parts of aluminum oxide, 10-15 parts of calcium oxide, 1-2 parts of magnesium oxide, 1-2 parts of sodium oxide, 1-2 parts of zinc oxide, 1-2 parts of sodium carboxymethyl cellulose and 1-2 parts of sodium hexametaphosphate.
[0061] In some embodiments, the surface glaze layer is sintered on the base glaze layer by a surface glaze material, and the surface glaze material includes, by mass: 15-20 parts of aluminum oxide, 55-60 parts of silicon dioxide, 2-3 parts of potassium oxide, 10-15 parts of aluminum oxide, 10-15 parts of calcium oxide, 1-2 parts of magnesium oxide, 1-2 parts of sodium oxide, 1-2 parts of zinc oxide, 1-2 parts of cesium oxide, 1-2 parts of sodium carboxymethyl cellulose and 1-2 parts of sodium hexametaphosphate.
[0062] The present invention also provides a preparation process of skin glaze ceramic tiles, comprising the following steps: spraying a protective glaze on the surface of the surface glaze layer, sintering at 1200-1300°C, and then grinding and forming to obtain the skin glaze ceramic tiles; the spraying amount of the protective glaze on the surface of the surface glaze layer is 300-400g / m 2 .
[0063] In fact, when preparing skin-glazed ceramic tiles, the tile body needs to be pressed into shape and dried in advance, then the base glaze is added to the tile body, and then the surface glaze is added on the surface of the base glaze. Finally, the protective glaze is added and sintered uniformly in the kiln.
[0064] Preparation Example 1
[0065] This preparation example 1 provides a method for preparing modified silicon oxynitride powder, comprising the following steps:
[0066] S0, silicon oxide with an average particle size of 5 μm was ball-milled in an oxygen atmosphere at 150°C with zirconium oxide as the ball at a ball-to-material ratio of 20:1 for 30 minutes, and then the ball-milled silicon oxide was transferred to an oxygen atmosphere at 350°C for preheating for 3 hours;
[0067] S1. The preheated silicon oxide powder is placed in an atmosphere furnace with a nitrogen flow rate of 5 L / min. The atmosphere furnace is heated to 1450°C at a rate of 5°C / min and then kept warm for 20 hours. The furnace is cooled to 250°C and then vacuumed for degassing for 2 hours. The powder is ground to an average particle size of 10 μm and then cooled to room temperature to obtain silicon oxynitride powder. The mass content of nitrogen in the silicon oxynitride powder is 35.74% by elemental analysis.
[0068] S2, dispersing the silicon oxynitride powder in an ethanol solution of hexadecyltrimethylammonium chloride (CAS: 112-02-7; the mass ratio of silicon oxynitride powder to hexadecyltrimethylammonium chloride is 1:0.15) at a frequency of 20 kHz for 15 minutes, keeping the mixture in a water bath at 45° C. for 1 hour, and then separating, washing, and drying to complete the surface activation of the silicon oxynitride powder;
[0069] S3, adding the surface activated silicon oxynitride powder into tetraethyl orthosilicate at a solid-liquid ratio of 0.2 g / mL, ultrasonically treating at a frequency of 20 kHz for 15 min, keeping warm in a 50°C water bath for 15 min, filtering, separating and washing, and drying in a hot air drying oven at 100°C to constant weight to obtain a modified precursor;
[0070] S4, nano-molybdenum sulfide with an average particle size of 20 nm is placed in a saturated sodium hydroxide solution at a solid-liquid ratio of 0.2 g / mL, ultrasonically treated at a frequency of 30 kHz for 10 min, stirred and mixed for 1 h, separated and dried in a vacuum environment at 50° C. to constant weight, thereby completing the surface hydroxyl modification of the nano-molybdenum sulfide;
[0071] S5. The nano-molybdenum sulfide after surface hydroxyl modification and the modified precursor are mixed in a mass ratio of 1:22 and put into anhydrous ethanol, and ultrasonically mixed at a frequency of 30 kHz for 30 minutes, and then separated and dried to obtain a modified intermediate; the modified intermediate is transferred to an atmosphere furnace, kept warm in a nitrogen atmosphere at 1450°C for 6 hours, vacuum degassed and cooled to room temperature, and then ground to obtain a modified silicon oxynitride powder with an average particle size of 10 μm.
[0072] Preparation Example 2
[0073] This preparation example 2 provides a method for preparing modified silicon oxynitride powder, comprising the following steps:
[0074] S0, silicon oxide with an average particle size of 5 μm was ball-milled in an oxygen atmosphere at 150°C with zirconium oxide as the ball at a ball-to-material ratio of 20:1 for 30 minutes, and then the ball-milled silicon oxide was transferred to an oxygen atmosphere at 350°C for preheating for 3 hours;
[0075] S1. The preheated silicon oxide powder is placed in an atmosphere furnace with a nitrogen flow rate of 6 L / min. The atmosphere furnace is heated to 1450°C at a rate of 5°C / min and then kept warm for 20 hours. The furnace is cooled to 250°C and then vacuumed for degassing for 2 hours. The powder is ground to an average particle size of 10 μm and then cooled to room temperature to obtain silicon oxynitride powder. The mass content of nitrogen in the silicon oxynitride powder is 37.18% by elemental analysis.
[0076] S2, dispersing the silicon oxynitride powder in an ethanol solution of hexadecyltrimethylammonium chloride (CAS: 112-02-7; the mass ratio of silicon oxynitride powder to hexadecyltrimethylammonium chloride is 1:0.15) at a frequency of 20 kHz for 15 minutes, keeping the mixture in a water bath at 45° C. for 1 hour, and then separating, washing, and drying to complete the surface activation of the silicon oxynitride powder;
[0077] S3, adding the surface activated silicon oxynitride powder into tetraethyl orthosilicate at a solid-liquid ratio of 0.2 g / mL, ultrasonically treating at a frequency of 20 kHz for 15 min, keeping warm in a 50°C water bath for 15 min, filtering, separating and washing, and drying in a hot air drying oven at 100°C to constant weight to obtain a modified precursor;
[0078] S4, nano-molybdenum sulfide with an average particle size of 20 nm is placed in a saturated sodium hydroxide solution at a solid-liquid ratio of 0.2 g / mL, ultrasonically treated at a frequency of 30 kHz for 10 min, stirred and mixed for 1 h, separated and dried in a vacuum environment at 50° C. to constant weight, thereby completing the surface hydroxyl modification of the nano-molybdenum sulfide;
[0079] S5. The nano-molybdenum sulfide after surface hydroxyl modification and the modified precursor are mixed in anhydrous ethanol at a mass ratio of 1:22, and ultrasonically mixed at a frequency of 30 kHz for 30 minutes. After separation and drying, the modified silicon oxynitride powder with an average particle size of 10 μm is obtained by grinding.
[0080] Preparation Example 3
[0081] This preparation example 3 provides a method for preparing modified silicon oxynitride powder, comprising the following steps:
[0082] S0, silicon oxide with an average particle size of 5 μm was ball-milled in an oxygen atmosphere at 150°C with zirconium oxide as the ball at a ball-to-material ratio of 20:1 for 30 minutes, and then the ball-milled silicon oxide was transferred to an oxygen atmosphere at 350°C for preheating for 3 hours;
[0083] S1. The preheated silicon oxide powder is placed in an atmosphere furnace with a nitrogen flow rate of 5 L / min. The atmosphere furnace is heated to 1450°C at a rate of 5°C / min and then kept warm for 20 hours. The furnace is cooled to 250°C and then vacuumed for degassing for 2 hours. The powder is ground to an average particle size of 10 μm and then cooled to room temperature to obtain modified silicon oxynitride powder. Elemental analysis shows that the mass content of nitrogen in the modified silicon oxynitride powder is 35.74%.
[0084] Example 1 to Example 5
[0085] Embodiments 1 to 5 of the present invention respectively provide a protective glaze, wherein the weight fractions of the chemical compositions are shown in Table 1 below.
[0086] Table 1 Chemical composition of protective glaze in Examples 1 to 5
[0087] Example 1 Example 2 Example 3 Example 4 Example 5 Silicon dioxide 50 55 60 54 56 Alumina 7 8 10 8 9 Boron Oxide 1 1.5 2 1.3 1.4 Sodium oxide 2 2.3 3 2.5 2.4 Potassium Oxide 1 1.6 2 1.7 1.8 Calcium Oxide 15 17 20 16 17 Magnesium Oxide 1 1.6 2 1.4 1.2 Lithium Oxide 1 1.7 2 1.8 1.4 Cesium Oxide 0.1 0.3 0.5 0.4 0.3 Barium Oxide 0.1 0.4 0.5 0.3 0.4 Zinc Oxide 1 1.8 2 1.7 1.2 Modified silicon oxynitride powder 1 1.7 2 1.4 1.5 Sodium Carboxymethyl Cellulose 1 1.4 2 1.3 1.8 Sodium Hexametaphosphate 1 1.3 2 1.2 1.6
[0088] Among them, the modified silicon oxynitride powder used in Examples 1 to 3 is prepared in Preparation Example 1, the modified silicon oxynitride powder used in Example 4 is prepared in Preparation Example 2, and the modified silicon oxynitride powder used in Example 5 is prepared in Preparation Example 3.
[0089] Comparative Example 1
[0090] This comparative example 1 provides a protective glaze, which is different from example 2 in that no modified silicon oxynitride powder is added in comparative example 1.
[0091] Comparative Example 2
[0092] This comparative example 2 provides a protective glaze, which is different from Example 2 in that no modified silicon oxynitride powder is added in comparative example 2, but 1.7 parts of nano molybdenum sulfide is added.
[0093] Application Examples 1 to 7
[0094] This application example 1 provides a method for preparing skin glaze ceramic tiles, comprising the following steps:
[0095] Y1. Prepare a base glaze material, wherein the chemical composition, by mass, includes 27 parts of aluminum oxide, 53 parts of silicon dioxide, 2.5 parts of potassium oxide, 14 parts of aluminum oxide, 12 parts of calcium oxide, 1.2 parts of magnesium oxide, 1.6 parts of sodium oxide, 1.5 parts of zinc oxide, 1.1 parts of sodium carboxymethyl cellulose and 1.5 parts of sodium hexametaphosphate;
[0096] Y2. Prepare a glaze material, wherein the chemical components, by mass, include 19 parts of aluminum oxide, 58 parts of silicon dioxide, 2.3 parts of potassium oxide, 12 parts of aluminum oxide, 14 parts of calcium oxide, 1.5 parts of magnesium oxide, 1.6 parts of sodium oxide, 1.2 parts of zinc oxide, 1.5 parts of cesium oxide, 1.4 parts of sodium carboxymethyl cellulose and 1.4 parts of sodium hexametaphosphate;
[0097] Y3. Spray the base glaze, surface glaze and protective glaze (prepared by Examples 1 to 5 and Comparative Examples 1 to 2, respectively) on the surface of the ceramic tile body in sequence, transfer them to a kiln for high-temperature sintering at 1284°C, and then grind the edges to obtain skin-glazed ceramic tiles.
[0098] Performance Testing
[0099] The skin-glazed ceramic tiles prepared in Application Examples 1 to 7 were tested for surface gloss using a WGG60-Y4 gloss meter, and the test results are shown in Table 2 below. The skin-glazed ceramic tiles were polished for 7500 revolutions using a wear tester, and the surface effect was observed, and the gloss attenuation rate was calculated, as shown in Table 2 below.
[0100] Table 2 Surface performance test of skin glaze ceramic tiles
[0101] Glossiness before polishing (°) Gloss attenuation rate (%) Brick surface effect after polishing Application Example 1 29.4 2.38 No obvious traces Application Example 2 31.5 2.24 No obvious traces Application Example 3 31.9 2.31 No obvious traces Application Example 4 29.7 8.67 No obvious traces Application Example 5 30.6 12.76 Subtle traces Application Example 6 31.5 24.51 Obvious traces Application Example 7 32.8 13.84 Subtle traces
[0102] It can be seen from Table 2 that the surface gloss of the skin-glazed ceramic tiles provided by the present invention is between 25-35 degrees, and the gloss attenuation rate after polishing meets the requirements, which means that the skin-glazed ceramic tiles provided by the present invention can be used well in indoor environments for a long time when used for a long time, and the surface gloss will not drop significantly due to use time and appear matte.
[0103] As can be seen from Table 2, the modified silicon oxynitride powder used in the protective glaze in Application Example 4 was not subjected to surface nitridation, which to a certain extent affected the microscopic integrity of the surface of the protective glaze layer after high-intensity grinding, thereby affecting the surface gloss after grinding. The modified silicon oxynitride powder used in the protective glaze in Application Example 5 was not compounded with nano-molybdenum sulfide, which affected the surface strength of the protective glaze layer. In Application Example 6, no modified silicon oxynitride powder was added, and the wear resistance and gloss retention of the protective glaze layer decreased significantly, which shows the necessity of modified silicon oxynitride powder in the protective glaze layer. In Application Example 7, nano-molybdenum sulfide was directly added, which can improve the wear resistance compared with Application Example 6.
[0104] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.
Claims
1. A skin glaze ceramic tile, characterized in that: It includes a ceramic tile body and a skin glaze layer sintered and formed on at least one surface of the ceramic tile body, wherein the skin glaze layer includes a bottom glaze layer, a surface glaze layer and a protective glaze layer sequentially formed along the ceramic tile body; The protective glaze layer is sintered and formed by a protective glaze on the surface glaze layer. The protective glaze includes, by mass, 50-60 parts of silicon dioxide, 7-10 parts of aluminum oxide, 1-2 parts of boron oxide, 2-3 parts of sodium oxide, 1-2 parts of potassium oxide, 15-20 parts of calcium oxide, 1-2 parts of magnesium oxide, 1-2 parts of lithium oxide, 0.1-0.5 parts of cesium oxide, 0.1-0.5 parts of barium oxide, 1-2 parts of zinc oxide, 1-2 parts of modified silicon oxynitride powder, 1-2 parts of adhesive and 1-2 parts of dispersant.
2. The skin-glazed ceramic tile according to claim 1, characterized in that: The adhesive includes at least one of sodium carboxymethyl cellulose, polyvinyl alcohol, sodium silicate, methyl cellulose, and sodium alginate; and / or the dispersant includes at least one of sodium polypropylene alcohol, sodium hexametaphosphate, and ethylenediamine di-o-hydroxyphenyl acetate; and / or the average particle size of the modified silicon oxynitride powder is 1-20 μm.
3. The skin glaze ceramic tile according to claim 1, characterized in that: The preparation method of the modified silicon oxynitride powder comprises: performing surface activation on the silicon oxynitride powder, stirring and dispersing the powder in tetraethyl orthosilicate, and then separating to obtain a modified precursor; performing surface hydroxyl modification on nano-molybdenum sulfide, ultrasonically mixing and dispersing the powder with the modified precursor, and then separating and drying to obtain a modified intermediate; and performing complex nitridation on the modified intermediate to obtain the modified silicon oxynitride powder.
4. The skin glaze ceramic tile according to claim 3, characterized in that: The preparation method of silicon oxynitride powder comprises the following steps: preheating silicon oxide in an oxygen atmosphere at 300-400° C. for 2-3 hours, heating the preheated silicon oxide to 1400-1500° C. at a rate of 5-10° C. / min in a nitrogen atmosphere, keeping the temperature for 20-30 hours, vacuum degassing at 200-300° C. for 1-2 hours, and grinding to obtain silicon oxynitride powder.
5. The skin-glazed ceramic tile according to claim 4, characterized in that: The silicon oxide has a particle size of 1-10 μm; and / or, the nitrogen-containing atmosphere includes one of nitrogen and ammonia; and / or, the silicon oxide is ball-milled in an oxygen atmosphere at 100-200° C. for 30-40 minutes and then preheated in an oxygen atmosphere at 300-400° C. for 2-3 hours.
6. The skin-glazed ceramic tile according to claim 3, characterized in that: The mass content of nitrogen in the silicon oxynitride powder is 20-40%; and / or, the silicon oxynitride powder is surface activated in an activator, and the activator includes at least one of hexadecyltrimethylammonium chloride, lauryldimethylamine oxide, and octadecyldimethylbenzylammonium chloride; and / or, after the silicon oxynitride powder is surface activated, it is stirred and dispersed in tetraethyl orthosilicate at a solid-liquid ratio of 0.1-0.3g / mL; And / or, after stirring and dispersing in tetraethyl orthosilicate, separating and washing, and drying at 80-100° C., a modified precursor is obtained.
7. The skin-glazed ceramic tile according to claim 3, characterized in that: The average particle size of the nano-molybdenum sulfide is 1-100nm; and / or, the surface hydroxyl group of the nano-silicon sulfide is modified in an alkaline solution, and the solute in the alkaline solution includes one of sodium hydroxide and potassium hydroxide; and / or, when the surface of the nano-molybdenum sulfide is modified and then ultrasonically mixed with a modified precursor, the modified nano-molybdenum sulfide and the modified precursor are ultrasonically mixed in anhydrous ethanol; and / or, the mass ratio of the nano-molybdenum sulfide to the modified precursor is 1:(20-25).
8. The skin glaze ceramic tile according to claim 3, characterized in that: When the modified intermediate is subjected to complex nitridation to obtain the modified silicon oxynitride powder, the modified intermediate is kept warm in a nitrogen atmosphere or an ammonia atmosphere at 1400-1500° C. for 5-10 hours, and then vacuum degassed, cooled and ground to obtain the modified silicon oxynitride powder.
9. The skin-glazed ceramic tile according to claim 1, characterized in that: The base glaze layer is formed by sintering a base glaze material on the ceramic tile body, and the base glaze material includes, by mass, 20-30 parts of aluminum oxide, 50-55 parts of silicon dioxide, 2-3 parts of potassium oxide, 10-15 parts of aluminum oxide, 10-15 parts of calcium oxide, 1-2 parts of magnesium oxide, 1-2 parts of sodium oxide, 1-2 parts of zinc oxide, 1-2 parts of sodium carboxymethyl cellulose and 1-2 parts of sodium hexametaphosphate; and / or, the surface glaze layer is formed by sintering a surface glaze material on the base glaze layer, and the surface glaze material includes, by mass, 15-20 parts of aluminum oxide, 55-60 parts of silicon dioxide, 2-3 parts of potassium oxide, 10-15 parts of aluminum oxide, 10-15 parts of calcium oxide, 1-2 parts of magnesium oxide, 1-2 parts of sodium oxide, 1-2 parts of zinc oxide, 1-2 parts of cesium oxide, 1-2 parts of sodium carboxymethyl cellulose and 1-2 parts of sodium hexametaphosphate.
10. A process for preparing the skin glaze ceramic tile according to any one of claims 1 to 9, characterized in that: The following steps are involved: The protective glaze is sprayed on the surface of the glaze layer, and then sintered at 1200-1300°C and polished to form a skin glaze ceramic tile; the spraying amount of the protective glaze on the surface of the glaze layer is 300-400g / m 2 .
Citation Information
Patent Citations
Glaze composition, skin glaze ceramic tile and preparation method of skin glaze ceramic tile
CN115557701A
Soft light glazed tile with skin texture and preparation method thereof
CN114315425A
Micro-crystal micro-gloss glaze, micro-gloss ceramic rock plate with ultra-flat and fine glaze surface and preparation method of micro-crystal micro-gloss glaze and micro-gloss ceramic rock plate
CN115838245A
Digital low-light stone ceramic tile with skin texture as well as preparation method and application of digital low-light stone ceramic tile
CN116693330A
Warm jade skin glaze ceramic tile and preparation method thereof
CN117361880A